Estudio de factibilidad para la fabricación y exportación de camuflados tipo cargo para caballero hacia el mercado ecuatoriano - Solano Sepúlveda, Erika Johana; Sotelo Súarez, Julián Manuel (Universidad Antonio Nariño, 2024)
The present research work was carried out in the company ̈Manufacturas Destroyer ̈located in the city of Bogota, Colombia. The purpose is to carry out a correct study to determine the feasibility of exporting camouflaged cargo type for men to the Ecuadorian market. This work was based on the study of the Ecuadorian country and international demand in order to determine the macro environment.